Association of Rs763780 Polymorphism of Gene IL17F with the Risk of Developing Rheumatoid Arthritis in Uzbekistan (Global Journal of Medical Research, 2021)
As a result of the study conducted, it was witnessed that the G allele and the heterozygous A / G genotype of the IL17F gene (rs763780) among patients with RA are significantly higher than in the control group. In particular, the most significant discrepancies were registered in patients with articular-visceral form of the disease whom the G allele exceeded the proportion of carriage in the control statistically significantly 2.58 times (χ2 = 4.512; P = 0.037; OR = 2.58; 95% CI: 1.076 -6.188). On the part of the heterozygous genotype A / G there was a clear tendency to increase its frequency by more than twice (χ2 = 2.011; P = 0.165; OR = 2.068; 95% CI: 0758-5.645) which in turn indicates the possible participation of the studied polymorphism in the pathogenesis of RA.
Keywords: rheumatoid arthritis (RA); rs763780 polymorphism of gene IL17F; carriage; allele; genotype; develoment risk